Roam - Somers-Willett, Susan B. A., 1973- (Crab Orchard award series in poetry., 2006)
Roam explores the loss of a parent to cancer and the resulting uprootedness that loss can create. In searching for a sense of home and belonging, this collection of free verse looks both inward and outward, to landscapes rural and urban, and speaks in haunting and musical lyrics. Unexpected voices emerge from history and myth-those of Joan of Arc, Ophelia, Circe, Daedalus and Icarus, and Achilles' mother, Thetis-and mingle with the author's own voice. From the naming of the first woman, Eve, to the naming of the first European child born in the Americas, Virginia Dare, thes.